Analysis of the Substantive and Procedural Elements of the Principle of Legality - Fekolli, Saimir; Biti, Bledar; Ganaj, Francesk (European Scientific Journal, ESJ, 2019)
The law, in general, and more specifically the criminal law is guided by some basic principles. One of the principles, which is most important, is the principle of legality which represents the criminal discipline regarding the abolition of the retrospective power of the unfavorable norm. This can also be considered as the bad retrospective power. This paper focuses on analyzing this principle in the doctrinal aspect. The analysis focuses on how the principle of legality is enforced and interpreted on International Law and Albanian Criminal Law. This paper also aims to analyze different decisions of the European Court of Justice and Constitutional Court of Albania to find out the effect of this principle.